2014
DOI: 10.1007/s00280-014-2583-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of the novel cyclin-dependent kinase inhibitor dinaciclib in combination with rituximab in relapsed/refractory chronic lymphocytic leukemia patients

Abstract: Limited data from this study shows dinaciclib in combination with rituximab was well tolerated and revealed encouraging clinical activity in relapsed/refractory CLL patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…Although clinical trials showed that dinaciclib displayed tolerable toxicity (Parry et al, 2010;Nemunaitis et al, 2013;Fabre et al, 2014;Asghar et al, 2015;Kumar et al, 2015), some reports of randomized phase 2 trials of dinaciclib have been disappointing (Mita et al, 2014) with no significant response, particularly in patients with non-small cell lung cancer (Stephenson et al, 2014) or acute lymphoblastic leukemia (Gojo et al, 2013). In this study, we showed that neither ABT-737 nor dinaciclib is a potent cytotoxic agent when used alone and that efficacy was poor at the clinically achievable range.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Although clinical trials showed that dinaciclib displayed tolerable toxicity (Parry et al, 2010;Nemunaitis et al, 2013;Fabre et al, 2014;Asghar et al, 2015;Kumar et al, 2015), some reports of randomized phase 2 trials of dinaciclib have been disappointing (Mita et al, 2014) with no significant response, particularly in patients with non-small cell lung cancer (Stephenson et al, 2014) or acute lymphoblastic leukemia (Gojo et al, 2013). In this study, we showed that neither ABT-737 nor dinaciclib is a potent cytotoxic agent when used alone and that efficacy was poor at the clinically achievable range.…”
Section: Discussionmentioning
confidence: 71%
“…Several CDK inhibitors, including dinaciclib (Merck, Kenilworth, NJ), palbociclib (Pfizer, New York, NY), abemaciclib (Lilly, Southlake, TX), BAY1000394 (Bayer Healthcare, Leverkusen, Germany), and ribociclib (Novartis Pharmaceuticals Corp., Basel, Switzerland) are currently in clinical trials for various advanced cancers (Asghar et al, 2015, Gallorini et al, 2012. Dinaciclib inhibits CDKs 1, 2, 5, and 9 and entered phase 2 and 3 clinical trials in a range of malignancies and displayed tolerable toxicity (Parry et al, 2010;Nemunaitis et al, 2013;Fabre et al, 2014;Asghar et al, 2015, Kumar et al, 2015. Parry et al (2010) also showed that dinaciclib inhibited cell proliferation and cell-cycle progression in multiple tumor cell lines across a broad range of tumor types with different genetic backgrounds and induced regression of established solid tumors in mouse models.…”
Section: Introductionmentioning
confidence: 99%
“…Pan-CDK inhibitors have been studied intensively over the past decade, and although there is a strong mechanistic rationale and promising preclinical data, compounds in development have not yet met expectations in clinical trials. Dinaciclib, an inhibitor of CDKs 1, 2, 5, and 9, has shown encouraging clinical activity as monotherapy and in combinations in phase I trials in advanced malignancies and leukaemia (Nemunaitis et al , 2013; Fabre et al , 2014); however, phase II studies in non-SCLC and advanced breast cancer were disappointing (Mita et al , 2014; Stephenson et al , 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Dinaciclib has already been evaluated in clinical trials and results show that has encouraging activity in relapsed/refractory CLL (Fabre, et al 2014, Flynn, et al 2015.…”
Section: Discussionmentioning
confidence: 99%